Recursos didácticos audiovisuales en el aprendizaje de la Matemática del quinto A de la escuela Matilde Hidalgo de Procel, Loja 2022-2023 - Carrión Prado, Yulexi Jamileth (2023)
The present work aims to analyze the contribution of audiovisual teaching resources for learning mathematics basing on an explanatory model in a sample of students to fifth year from Matilde Hidalgo de Procel School by building an improved learning of the subject. Three different specific objectives were developed; firstly, specify the audiovisual didactic resources that have the greatest impact on students’ learning of mathematics, then prepare and assess the improvement proposal on the impact of audiovisual aids in learning of the subject. The methodological approach of the research adopts a descriptive structure, of non-experimental design, from a mixed approach; likewise, the inductive, deductive, analytical, synthetic, and statistical methods were used. For this purpose, it has been applied the structured interview and a pre- and post – evaluation questionnaire, for that I work with a type of non-probabilistic sampling represented by 22 students and 1 teacher. The subsequent analysis of the data has allowed me to determine that through the application of audiovisual didactic resources, the learning of mathematics in students can be deepened, reinforced and improved, it is concluded that the use of audiovisual didactic resources allows the teacher to create a pleasant and active class environment where students can demonstrate their abilities and thereby achieve meaningful learning. Keywords: audiovisual didactic resources, teaching-learning process, mathematics, methods, techniques, abilities.